Depressive syndrome and eating disorders in women - Zusman, Lillyana (1999)
It is alarming to see the increase of the depressive syndrome and eating disorders in women. The changes in the traditional feminine attitude, concerning maternity and the fulfillment of taking care of the family love, it's identity acquires passively since early childhood and the stereotype of establishing an association between depression and other eating disorders. The article establishes "muteness of the voice", as a strategy learned since childhood and strengthened in adolescence to silence, reprieve and ser apart the awakening to the sensations produced by the body towards desire and sexual pleasures. The body responds as an alternative language of somatic characteristics through which it intends to splitting the emotional message.